2008
DOI: 10.1007/s00467-008-0799-9
|View full text |Cite|
|
Sign up to set email alerts
|

Duration of oliguria and anuria as predictors of chronic renal-related sequelae in post-diarrheal hemolytic uremic syndrome

Abstract: Prior long-term retrospective studies have described renal sequelae in 25-50 % of post diarrheal hemolytic uremic syndrome (D+HUS ) survivors, but the ability to predict the likelihood of chronic renal related sequelae at the time of hospital discharge is limited. We surveyed 357 children in our HUS registry who had survived an acute episode of D+HUS and were without end stage renal disease (ESRD) at the time of hospital discharge. Of the 357 patients surveyed, 159 had at least one year (mean 8.75 years) of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 16 publications
3
45
1
14
Order By: Relevance
“…[8][9][10] Between 20% and 30% of patients have longterm kidney sequelae, including proteinuria, high blood pressure, and a reduced glomerular filtration rate. 2,[10][11][12] Several studies have attempted to establish predictors of a poor prognosis in terms of mortality and kidney disease progression in patients with typical HUS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[8][9][10] Between 20% and 30% of patients have longterm kidney sequelae, including proteinuria, high blood pressure, and a reduced glomerular filtration rate. 2,[10][11][12] Several studies have attempted to establish predictors of a poor prognosis in terms of mortality and kidney disease progression in patients with typical HUS.…”
Section: Discussionmentioning
confidence: 99%
“…2,[10][11][12] Several studies have attempted to establish predictors of a poor prognosis in terms of mortality and kidney disease progression in patients with typical HUS. 8,9 The studies conducted by Oakes et al in 2006 and demonstrated that leukocytosis and mild anemia at the time of admission to the hospital were associated with mortality, and the duration of oliguria and/or anuria were predictors of kidney morbidity in the long term. 8,9 In endemic regions, many family cases of HUS are caused by the Shiga toxin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hastaların vücut ağırlıkları, kan basıncı ölçümleri, günlük sıvı alımları ve idrar miktarları takip edildi. İdrar miktarının <500 ml/1,73m 2 /gün olması oligüri olarak (6) ve < 15 ml/gün olması anüri olarak kabul edildi (7). Sistolik ve diastolik kan basıncı ölçümlerinin yaşa ve cinse göre >95th persantil olması hipertansiyon olarak tanımlandı (8).…”
Section: Gereç Ve Yöntemunclassified